Pair check (pc) modelling with worksheet participants media in the training of writing class action research (PTK) - Syahrul R; Elfia Sukma; Utami Dewi Pramesti* (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This article describes the results and the implementation of the paircheck method with a work sheet of participants which is the result of community service with the title “Training of Scientific Writing for Teachers of SD Tawar Timur Kota Padang West Sumatra.” In the process, teachers are guided in writing classroom action research through a participant’s worksheet that contains a summary of materials and direct exercise columns with a paired check table. Participants in this training are 26 teachers from 3 public elementary schools in East Tawar area, Padang City. The method used is qualitative-descriptive that explains the final outcome and the implementation of the training. After three days of training, the participants' writing skills increased, which was proved by pre-test and post-test.